A Proposal of An Analytical Conflict Management Model for the Chinese Context - Falcão, P. F.; Lopes da Costa, R. (ICABM2020 - International Conference of Applied Business and Management, 2020)
China’s culture is different from Western cultures, with various implications including conflict management styles. Many conflict management studies have been based in a set of models with the same or similar assumptions, namely two axis related with concern for self and concern for the other or for the relationship with the other, that produce four or five conflict management styles (e.g., Rahim 2002). However, those similar models do not reflect China’s culture. This study aims to create a model for conflict management styles structure definition that is adapted to Chinese culture. After analyzing the existing literature, 19 interviews with relevant experts in the field of conflict management in the Chinese context were conducted. This was followed by the elaboration of a structure aimed at gathering, simplifying and explaining the main dynamics of Chinese decision making, allowing for a better understanding of the dynamics between different elements identified. Finally, a model was created that aims to provide a possible explanation to how and why the identified mechanics work and how they can assist a given individual in a conflict management situation. The proposed model is original in the sense that it adapts conflict management styles structure originally reflecting Western cultures (e.g., Rahim, 2002) to the Chinese culture.Findings show that extreme positions in a relationship or negotiation are eliminated. There is no room for attempts of dominating another’s decision or ignore our own interests in favor of others. As Harmony and Guanxi are pillars for any Chinese social living, they were selected as the two axes of the conflict management styles definition, which, based on the literature review and interviews findings, led to the creation of the SETH (Stability, Expansion, Transformation and Hindrance) model of conflict management styles.